Функциональная гистология пищеварительной системы факультативного кровососа Androlaelaps casalis (Parasitiformes, Gamasoidea) - Старовир, И.С. (Вестник зоологии, 1981)
Morphofunctional changes in the mid-gut epithelial cells and the diverticulum are studied in Androlaelaps casalis. It is determined that the epithelium cells of the guts are represented by three types: secretory, digestive and nondifferentiated. Considerable differences in the cell structure are observed in fasting mites during nutrition at different stages of digestion depending on the degree of cell filling with nutrients. Such functional changes inside the cells are initiated by fusion of small vacuoles into large ones in which food granules are formed. The process of intracellular digestion in the granules proceeds asynchronously. Certain epithelial cells in A. casalis are torn away quickly to the gut lumen. Most probably the mites are chiefly characterized not only by abdominal but also intracellular food digestion.